2021
DOI: 10.1007/s00405-021-07023-w
|View full text |Cite
|
Sign up to set email alerts
|

Auditory processing in normally hearing individuals with and without tinnitus: assessment with four psychoacoustic tests

Abstract: Purpose In most cases, tinnitus co-exists with hearing loss, suggesting that poorer speech understanding is simply due to a lack of acoustic information reaching the central nervous system (CNS). However, it also happens that patients with tinnitus who have normal hearing also report problems with speech understanding, and it is possible to suppose that tinnitus is to blame for difficulties in perceptual processing of auditory information. The purpose of the study was to evaluate the auditory pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
0
7

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 27 publications
6
16
0
7
Order By: Relevance
“…We also investigated elementary auditory perception and found that none of the threshold and supra-threshold tests performed (i.e., GDT, AM, FM, DLI, PTA noise , FPT and DPT) di↵ered significantly between the groups. Our data replicates several findings that also did not find di↵erences between chronic tinnitus and control groups (Bureš et al, 2019;Gilani et al, 2013;Moon et al, 2015;Raj-Koziak et al, 2022;Zeng et al, 2020). In all of these previous studies, elementary auditory stimuli were neither matched nor close to the tinnitus frequency.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We also investigated elementary auditory perception and found that none of the threshold and supra-threshold tests performed (i.e., GDT, AM, FM, DLI, PTA noise , FPT and DPT) di↵ered significantly between the groups. Our data replicates several findings that also did not find di↵erences between chronic tinnitus and control groups (Bureš et al, 2019;Gilani et al, 2013;Moon et al, 2015;Raj-Koziak et al, 2022;Zeng et al, 2020). In all of these previous studies, elementary auditory stimuli were neither matched nor close to the tinnitus frequency.…”
Section: Discussionsupporting
confidence: 85%
“…These tests are used in part in audiological practice, for example, to determine central processing disorders in children (Balen et al, 2019). However, there is little literature on these tests in tinnitus, but some studies using similar tests to ours did not find any di↵erences (e.g., Gilani et al, 2013;Raj-Koziak et al, 2022).…”
Section: Introductionmentioning
confidence: 57%
“…As EOAs são produzidas pelas CCEs da cóclea como resultado de processos de feedback mecânico ativo não linear, que podem ser espontâneos ou evocados por sons (Kemp et al, 1990;Norton et al, 1990;Serra et al, 2015). Para a avaliação comportamental do processamento auditivo, os relatos da relação com zumbido tangencia ao fato que este afeta certos aspectos do processamento auditivo como resolução temporal, percepção da fala no ruído e discriminação de frequência (Diges et al, 2017;Jain & Sahoo, 2014;Raj-Koziak et al, 2022).…”
Section: Discussionunclassified
“…The control group consisted of 20 healthy subjects (mean age = 30, SD = 10.7) with no tinnitus, hearing loss, and ear/health problems. The sample size used in the study was based on the G*power analysis 13 derived from the effect size in the previous study 14 on the 4 psychoacoustic measures in normal hearing individuals with and without tinnitus. For an effect size of 0.32, 14 and power of 0.51 at significance level ( P ) of .05, the sample size required was 42.…”
Section: Methodsmentioning
confidence: 99%